False spider mites (Acari: Tenuipalpidae) as pests on orchids (Phalaenopsis hybrids) in Poland - Łabanowski, Gabriel; Soika, Grazyna (Biological Letters, 2012)
So far, no false spider mites have been reported from orchids in Poland. This paper provides information about Tenuipalpus pacificus Baker, which was recorded for the first time in Poland, on Phalaenopsis hybrids imported from China. Diagnostic characters are also given for Brevipalpus phoenicis (Geijskes), which was up to this time not found on orchids in Poland. It was earlier found on orchids only in Hawaii. The types of injuries caused by false spider mites and results of chemical control of T. pacificus with various acaricides are given. The best results were observed after repeated treatment with Ortus 05 SC (fenpyroximate).